2021
DOI: 10.2174/1874944502114010012
|View full text |Cite
|
Sign up to set email alerts
|

The Psychological Impact of COVID-19 Pandemic on the Students of Saudi Arabia

Abstract: Background: Since the beginning of the coronavirus disease 2019 (COVID-19) pandemic, the numbers of cases and deaths worldwide have begun to increase, the closure of schools, universities, shops, workplaces, and the vast degree of precautionary actions, have left students feeling helpless, isolated, bored, and uncertain of what would happen to their academic advancement. Our study aims to assess the degree of the psychological impact of the COVID-19 pandemic on students in Saudi Arabia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…Such is the case of the recent study by Ozamiz-Etxebarria et al (2020) in which the snowball probability sample was used. In terms of sample size, the present investigation also bears some similarity to other studies on the impact of COVID-19 such as that of Alkhamees and Aljohani (2021) with N=336. Newly, it is possible to analyze the information by assuming limitations of the design and biases in the decision making process during neural network design.…”
Section: Limitationssupporting
confidence: 66%
See 1 more Smart Citation
“…Such is the case of the recent study by Ozamiz-Etxebarria et al (2020) in which the snowball probability sample was used. In terms of sample size, the present investigation also bears some similarity to other studies on the impact of COVID-19 such as that of Alkhamees and Aljohani (2021) with N=336. Newly, it is possible to analyze the information by assuming limitations of the design and biases in the decision making process during neural network design.…”
Section: Limitationssupporting
confidence: 66%
“…In Germany, 39.6% of university students reported increased stress levels (Schlichtiger et al, 2020). In Saudi Arabia, the prevalence of severe or extreme stress in this group was 13.4 and 10.7%, respectively (Alkhamees and Aljohani, 2021). A survey of a representative sample of the Spanish population demonstrated that 45.7% had experienced an elevation in their feeling of unease; further, the main reasons for seeking psychological help were the presence of depressive symptomatology (56.2%), and primarily, stress and anxiety (75.7%) (Balluerka et al, 2020).…”
Section: Introductionmentioning
confidence: 86%
“…Abdul Majeed and Moath S A, reported in their study that, during the early days of the pandemic, nearly one-fourth of students experienced moderate to severe symptoms of PTSD. Their findings could help guide schools and universities in implementing a clear, effective strategy for students to navigate the coming academic year and expand the efforts made on academic and psychological counseling, especially for the vulnerable populations [38]. Sanjeev K and Abdul Mohsen A, reported in their study that, the outbreak of COVID-19 pandemic has affected the mental health of dental interns.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, during the pandemic, moderate to high stress was prevalent (85%) among students studying in virtual classrooms in Saudi Arabia, especially females and university students [11]. Similarly, another two Saudi studies that were conducted during the pandemic showed that university students had significant symptoms of depression (48.8% and 56.3%) and anxiety (40.8% and 40.3%), especially female students [12,13]. Another study conducted among medical students found that 94% suffered from moderate to high perceived stress, and 47% had anxiety symptoms [22].…”
Section: Discussionmentioning
confidence: 99%